Low Bandgap Donor-Acceptor π-Conjugated Polymers From Diarylcyclopentadienone-Fused Naphthalimides - Li, Xiaolin; Guo, Jing; Yang, Longfei; Chao, Minghao; Zheng, Liping; Ma, Zhongyun; Hu, Yuanyuan; Zhao, Yan; Chen, Huajie; Liu, Yunqi (Frontiers in Chemistry, 2019)
Two novel aromatic imides, diarylcyclopentadienone-fused naphthalimides (BCPONI-2Br and TCPONI-2Br), are designed and synthesized by condensation coupling cyclopentadienone derivatives at the lateral position of naphthalimide skeleton. It has been found that BCPONI-2Br and TCPONI-2Br are highly electron-withdrawing acceptor moieties, which possess broad absorption bands and very low-lying LUMO energy levels, as low as −4.02 eV. On the basis of both building blocks, six low bandgap D-A copolymers (P1–P6) are prepared via Suzuki or Stille coupling reactions. The optical and electrochemical properties of the polymers are fine-tuned by the variations of donors (carbazole, benzodithiophene, and dithienopyrrole) and π-conjugation linkers (thiophene and benzene). All polymers exhibit several attractive photophysical and electrochemical properties, i.e., broad near-infrared (NIR) absorption, deep-lying LUMO levels (between −3.88 and −3.76 eV), and a very small optical bandgap (Egopt) as low as 0.81 eV, which represents the first aromatic diimide-based polymer with an Egopt of <1.0 eV. An investigation of charge carrier transport properties shows that P5 exhibits a moderately high hole mobility of 0.02 cm2 V−1 s−1 in bottom-gate field-effect transistors (FETs) and a typical ambipolar transport behavior in top-gate FETs. The findings suggest that BCPONI-2Br, TCPONI-2Br, and the other similar acceptor units are promising building blocks for novel organic semiconductors with outstanding NIR activity, high electron affinity, and low bandgap, which can be extended to various next-generation optoelectronic devices.